Effect of hardened steel grinding using aluminum oxide wheel under application of cutting fluid with corrosion inhibitors - Talon, Anthony Gaspar [UNESP]; Lopes, José Claudio [UNESP]; Tavares, André Bueno [UNESP]; Sato, Bruno Kenta [UNESP]; Rodrigues, Alessandro Roger; Genovez, Mário Celso; Dinis Pinto, Tiago Alexandre; de Mello, Hamilton José [UNESP]; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Springer Nature, 2019)
A new category of corrosion inhibitors has been formulated. It uses water to propagate and it has been generically referred as V-active VCI®. These inhibitors promote a greater lubricity and detergency effect, used as cutting fluids; it results in less diametrical grinding wheel wear and better workpiece finishing. It can also promote the corrosion protection of the workpiece and the machine tool since the referred substance creates a protective film on the metallic surfaces, eliminating protective oils application on the parts; thus, it permits the elimination of degreasing step, reducing the number of process steps, and minimizing the environmental impact. Furthermore, it has no risk to human’s health and it is biodegradable. This paper compares the performance of the cutting fluid with V-active VCI® to a synthetic standard fluid in grinding process of AISI 4340 steel using aluminum oxide (Al2O3) grinding wheel at three different feed rates (0.25, 0.50, and 0.75 mm/min). The comparison was carried out based on the surface roughness, roundness deviation, diametrical wheel wear, acoustic emission, optical microscopy, and microhardness. The results showed that the fluid with corrosion inhibitor kept stable as the feed rate increased, which evidence the high performance of the tested fluid in severe conditions. In addition, the fluid with corrosion inhibitor was superior in almost all evaluated variables; it was unexpected since the standard fluid is consolidated in industry.
Keywords: AISI 4340 steel; Aluminum oxide grinding wheel; External cylindrical grinding; Synthetic cutting fluid; Volatile corrosion inhibitor